(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
Abstract Religious education has become a public attention nowadays, especially after multidimentional crisis era which was characterized by moral and religious-ethics crisis. This chritical perception, indeed, can actually be regarded as the appreciation and confession to religious education as an urgent factor on context of actualizing students with high personality traits-based on God faith and good moral that actualized on daily attitudes. Unfortunately, that appreciation have not been equalized with the program to improve the religious education quality including the functioning of the vital components of the teaching-learning programs, examples the position of Pokjawas and supervisiory agents.This research tries to unpack the fact about the effectivity of Pkjawas on enhancing their ethos. Is it true that low quality of religious education is influenced by the ethos of Pokjawas that ineffective?